Tissue pO2 distributions in xenograft tumors dynamically imaged by Cherenkov-excited phosphorescence during fractionated radiation therapy - Xu Cao (Nature Portfolio, 2020)
Hypoxia in solid tumors is an important factor in radiation therapy resistance, but partial pressures of oxygen in the tissue are heterogenous and difficult to measure. Here the authors develop Cherenkov excited phosphorescence imaging using oxygen probe Oxyphor PtG4 to spatially track oxygen distributions in tumors during fractionated radiotherapy.